2015
DOI: 10.7555/jbr.29.20140076
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 overexpression in bone marrow mesenchymal stem cells promotes functional recovery in a rat model of peripheral nerve injury

Abstract: Transplantation of bone marrow mesenchymal stem cells (BMSCs) has been developed as a new method of treating diseases of the peripheral nervous system. While netrin-1 is a critical molecule for axonal path finding and nerve growth, it may also affect vascular network formation. Here, we investigated the effect of transplanting BMSCs that produce netrin-1 in a rat model of sciatic nerve crush injury. We introduced a sciatic nerve crush injury, and then injected 1×106 BMSCs infected by a recombinant adenovirus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, the low dose effect of exogenous Netrin-1 has not been tested yet. A more recent report showed that transplanting Netrin-1 overexpressing bone marrow mesenchymal stem cells to the injury site of rat sciatic nerve promotes axon regeneration and functional recovery [106]. Thus, the DCC and Unc5B knockdown data together with the data from Netrin-1 overexpressing stem cells suggests that Netrin-1 signaling promotes in vivo peripheral nerve regeneration.…”
Section: Netrin-1 Signaling In Peripheral Nerve Regenerationmentioning
confidence: 95%
“…However, the low dose effect of exogenous Netrin-1 has not been tested yet. A more recent report showed that transplanting Netrin-1 overexpressing bone marrow mesenchymal stem cells to the injury site of rat sciatic nerve promotes axon regeneration and functional recovery [106]. Thus, the DCC and Unc5B knockdown data together with the data from Netrin-1 overexpressing stem cells suggests that Netrin-1 signaling promotes in vivo peripheral nerve regeneration.…”
Section: Netrin-1 Signaling In Peripheral Nerve Regenerationmentioning
confidence: 95%
“…As we known, the abnormality of gene expression may increase the risk or severity of diseases [ 11 13 ]. Long noncoding RNAs (lncRNAs) have also been implicated in the crucial functions of various biological process involved in cancer susceptibility [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that transplantation of rat bone marrow mesenchymal stem cells (BMSCs) in a rat sciatic nerve injury model leads to the increased expression of BDNF and NGF at the injured site 43 . To investigate whether the engrafted iPSC-derived NCSCs and Schwann cells secrete neurotrophic factors (NFs) and participate in paracrine signaling in nerve regeneration, ELISA analyses of human neurotrophic factors NGF, BDNF, and CNTF were performed in the tissues within the implanted nerve conduits.…”
Section: Discussionmentioning
confidence: 99%